Hybrid gender colonization: The case of muxes. Issue 6 (23rd June 2022) - Ramirez, Jacobo; Munar, Ana María
Abstract: This study explores what can be learned from listening to and engaging deeply with muxes, the third gender of Mexico's indigenous Zapotec community. We examine indigenous peoples' forms of gender organizing, work, and activism through extensive fieldwork in the Isthmus of Tehuantepec in Oaxaca, Mexico and intellectual engagement with scholarship on gender, coloniality, and third space theory. The empirical case showcases how muxes organize and defend their gender identity vis‐à‐vis processes of colonization and hybridity. The findings reveal unique forms of indigenous knowledges, gender activism, and gender organizing and are categorized into six themes: language and subjectification ; work, social structure, and sexuality ; religion and myth ; esthetics and beauty ; work discrimination and gender‐based violence ; and emancipation and queer activism . The analysis explains the possibility of becoming of different gender/ethnic identities and multiple hybrid representations of agency and repression. We critically examine novel insights on how indigenous gender organizing is paradoxically appreciated and revered while also inciting discrimination and violence. The empirical findings help us reconsider theoretical discourses of ongoing (de)coloniality and the third space of gender organizing.